Experimental investigation of a novel evaporative cooling pad made of cement-free porous concrete. (15th January 2023) - Rahman, Md Sazan; MacPherson, Sarah; Lefsrud, Mark
Abstract: Greenhouse overheating is a major problem for dry climate agricultural setups during the summer months. Evaporative cooling is a convenient solution for controlling indoor temperature on hot and dry days. However, conventional evaporative cooling pad materials such as polymers, cellulose, and organic fibres present problems in terms of high carbon footprint, after-use disposal, and/or very limited lifespan. In this study, porous concrete was tested as a novel evaporative cooling pad material in an experimental wind tunnel with different inlet air temperatures at a constant air velocity (2.5 m s −1 ). The porous concrete evaporative cooling pad demonstrated the highest evaporative cooling capacity at −11.46 kW sensible cooling with 10.17 kW m −2 °C −1 cooling coefficient. It further exhibited an evaporation rate of 5.84 g s −1 with an evaporation coefficient of 1.56 m s −1 . The average cooling effectiveness was obtained as 0.97, where some inlet air conditions demonstrated negative enthalpy changes after evaporation. However, the maximum average enthalpy change was 10.97 kJ kg −1 . This novel evaporative cooling pad material showed the highest effectiveness when compared to conventional evaporative cooling pad systems reported in other studies. Highlights: Porous concrete is a prospective new evaporative cooling pad (ECP) material. A high cooling capacity (10.2 kW m −2 °C −1 heat transfer coefficient) was obtained. Cooling effectiveness reached 1.00 for inlet air temperatures ranging from 30 to 40 °C. The average cooling effectiveness was 0.97. Enthalpy changes showed (−)ve values with low inlet temperatures (30–40 °C).